Optimization of Bituminous Pavement Thickness using Mechanistic-Empirical Strain-Based Design Approach - Sahis, Manoj Kumar; Biswas, Partha Pratim (Civil Engineering Journal, 2021)
The pavement in this paper has been considered as a three layered system with the top layer of bituminous mix followed by unbound granular layer which rests on soil subgrade. The objective of the paper is to develop an optimization method based on mechanistic –empirical approach for estimation of bituminous and granular layer thickness. Two major modes of failure as rutting and fatigue have been considered for structural design of bituminous road section on strain based criteria. The vertical compressive strain on the top of subgrade and radial tensile strain at the bottom of bituminous layer have been determined by Boussinesq’s theory after transforming the three layered system in to a homogeneous system by Odemark’s method. The findings from the present study reveals that only one typical combination of bituminous and granular layer thickness is possible to save the pavement both against rutting and fatigue. The result of layer thickness obtained using present methodology was compared with other international published data and was found in good agreement. The pavement deflection as a performance indicator for the optimized pavement section thus obtained have been determined by Odemark's-Boussinesq's approach and compared with the deflection obtained using IITPAVE and KENPAVE software, which show reasonable good convergence. Doi: 10.28991/cej-2021-03091691 Full Text: PDF